Character and Fun Lecturing - Sulaiman, Sulaiman (Jurnal Ilmiah Peuradeun, 2017)
This study focused on Character and Fun lecturing at STAI-PTIQ Banda Aceh. The method used is qualitative descriptive approach. The subjects were 12 lecturers and three elements of leadership that are chosen by purposive sampling. The data collection techniques used is a triangulation technique. While the data were analyzed inductively so that the research results further emphasize the significance of the generalization. The results of the study revealed that; (1) Teaching skills of lecturers at STAI-PTIQ Banda Aceh supported character and fun lecture; (2) Most professors used cooperative lecturing model for the implementation of characters and fun lecture; (3) Some lecturers used a variety of media; and (4) conducive lecture situation was obtained by conducting a positive atmosphere lectures, both physical and nonphysical and democratic approach.